“Pay-What-You-Want” Pricing: Creating and Capturing Value Through Social Exchange - Ross, David Gaddis; Shin, Moonsik (Academy of Management Review, 2023)
In leading strategy theories, such as industry analysis and value capture theory, maximizing bargaining power with transaction partners is a critical driver of profitability. However, in recent years a new business model has emerged that contradicts this fundamental precept: With pay-what-you-want (PWYW) pricing, a seller allows a buyer to name any nonnegative price, even zero, for the seller’s product or service, and yet, enough buyers make voluntary positive payments, and of sufficient magnitude, that the seller may earn a substantial profit. Motivated by this development, we posit a theory of how value creation and value capture—though generally treated as distinct processes in strategy theory—are in fact strongly connected through the sociopsychological framing of a transaction: If a transaction is framed as a social exchange between the buyer and seller, the seller may capture more value with PWYW than if the seller posts a price or haggles with the buyer over terms in a market-based exchange. Our theory not only offers testable predictions about the conditions determining when PWYW will be successful but also extends strategy theory to consider social exchange as a mechanism for creating and capturing value.